Intensity of National Collegiate Athletics Association Division I women's soccer regular season games - De Oliveira Junior, S.; Soares de Sousa, V. G.; Coelho Rodrigues, J. F.; Ramos, N. C.; Cholewa, J. (The Journal of Strength and Conditioning Research, 2025)
This study assessed the intensity of National Collegiate Athletics Association Division I women's soccer regular season games. Thirteen regular season games of one team (18 subjects) were analyzed. Data were collected on average intensity, accumulated time per heart rate (HR) zone, and HR behavior throughout each game. The HR zones adopted were as follows: Z1 = 50-59%, Z2 = 60-69%, Z3 = 70-79%, Z = 80-89%, and Z5 = 90-100% of maximum HR (HRmax). One-way analysis of variance (ANOVA) with repeated measures was performed for comparisons between games, by time range, and by HR zone. Two-way ANOVA with repeated measures compared average intensity of each game and high- and low-intensity zones between the first and second half (p = 0.05). Average intensity of games was 89.08 ± 1.42% of HRmax, with minimum values of 67.12 ± 2.71% and maximum of 97.66 ± 0.98%, corresponding to 176 ± 2.13, 132.88 ± 5.50, and 193.66 ± 1.40 b·min-1, respectively. There was no significant difference in intensity between games (p = 0.09). Players spent more time in high-intensity zones Z5 and Z4. The average time in Z5 was 33 minutes 03 seconds ± 2 minutes 45 seconds and in Z4 was 18 minutes 24 seconds ± 2 minutes 34 seconds (p = 0.252). No significant differences were found in intensity comparisons between first and second half (p = 0.32) and 15-minute periods (p = 0.25). The intensity of games was high and constant throughout the 90 minutes in all games. Heart rate monitoring and planned substitutions during matches and training that focus on intermittent high-intensity activities and recovery, such as cold-water immersion may optimize match performance and prevent injuries.